b - 9 (b, 2010)
Autobiography of a woman social worker from Bangladesh.
Translation of Jowshan Ara Rahman's autobiography, Smritikatha : ekti ajana meye"--Editor's note.
Keywords: Rahman, Jowshan Ara; Women social workers -- Bangladesh; Women social workers -- Bangladesh -- Biography